Analisis Berkunjung Kembali pada Kebun Binatang Bandung dari Perspektif Harga Tiket dan Kelengkapan Satwa - Dita Amanah; B Lena Nuryanti; Ansari Harahap, Dedy (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2025)
This study aims to analyze the effect of ticket price and animal completeness on the decision to revisit Bandung Zoo. Involving 400 respondents from Bandung City, this study uses a quantitative approach through multiple linear regression analysis. The results show that both ticket price and animal completeness have a significant influence on visitors' decision to return. Ticket price factors tend to affect economic attractiveness, while animal completeness contributes to visitor experience and satisfaction. These findings provide strategic implications for Bandung Zoo managers in designing competitive pricing policies and ensuring the diversity of animal collections to increase visitor loyalty.